Prevalence of urinary tract infections among pregnant women in Iraq: meta-analysis study - hanoon, Noor (University of Thi-Qar Journal of Science, 2024)
Urinary tract infection (UTI) is the most prevalent bacterial infection in both community and hospital settings among women, especially pregnant women. It is characterized by a high incidence of treatment failure and relapses. The research aims to give an approximate percentage of the spread of the disease in various cities in Iraq, and compare it with other countries, and determine the risks of the disease and treatment for the mother and fetus. The 36 published articles have been reviewed in different regions of Iraq about pregnant women, made comparisons with other countries covered the period 2000–2023, and studied the risk factors, causative agents, and epidemiology of urinary tract infection. The results show that the rate of urinary tract infection is remarkably high in Iraq compared to other countries. UTI affects women between the ages (16-35years), Escherichia coli are the dominant bacteria that cause urinary tract infection, and education level has a significant effect on the prevalence of UTI.